Development of a Dribbling Technique Skills Training Model in Futsal Games for PJKR Students of the 2024 Class at Tadulako University - Resa, Muhammad; Murtono, Tri; Baton Lumbaa, Krisyanto; Purwanto, Didik (UNIB Press, 2026)
This study aims to develop a dribbling technique skill training model in futsal games for PJKR students of the 2024 class of Tadulako University. The method used is research and development (R&D) with the Borg and Gall model. The research subjects consisted of 10 students in the small group trial and 30 students in the large group trial. Data collection was carried out through a validation questionnaire from futsal experts, learning experts, and student response questionnaires, then analyzed using descriptive percentage techniques. The validation results showed that the assessment of futsal experts 1 and 2 was 63%, respectively, and the learning expert was 84%, with the category used. The results of the small group trial obtained a percentage of 80% and the large group 79%, both of which were in the category used. Based on these results, it can be concluded that the developed dribbling technique training model is feasible to use and can improve basic dribbling technique skills and student interest in futsal learning.